Endwall Contouring for Lowering the Thermal Load and Augmenting the Turbine Efficiency - Sunil, Arjun Kozhikkatil; Sunny, Tide Porathoor (UI Scholars Hub, 2024)
Endwall contouring having significance in delineating ideal endwalls competent in thermal load depletion is the focus of this study. We have successfully utilized non-axisymmetric contoured endwalls to enhance turbine performance by controlling the secondary flow characteristics in a blade passage through steady-state numerical hydrodynamics. The supreme endwall pattern could lower the gross pressure loss at the design stage and is related to the size of the top-loss location being productively lowered. The selective numerical shape change using multi-objective optimization at the most prominent locations resulted in contoured endwall geometry and a considerable reduction of thermal exchange in the vane passage and thermal load in the turbines. A non-axisymmetric contoured endwall achieves the highest net heat flux reduction and elevated aerodynamic performance with lower total pressure loss coefficients than an axisymmetric convergent contoured endwall at most locations of the endwall. In the present study, the ideal mass flow rate could pinpoint the endwall passage, contoured with outstanding axial turbine competence and longevity. Endwall contouring enhances turbine performance, and augmented efficiency is achieved with optimized shapes.